Analysis of Higher-Order-Thinking Skill (HOTS) Questions in the Class V Elementary Student's Books Theme 3 - Sarah Fazilla; Fauziana; Parida Hanum Siregar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The lack of higher-order thinking skills (HOTS) questions in student books causes students to be inadequate to solve HOTS questions. Hence, it resulted in the unachieved program of expected Curriculum 13 learning program, namely higher-order-thinking skills (HOTS) and 21st-century skills. This study aims to determine whether the questions in the Class V Student Book Theme 3,